KEPEMIMPINAN JOKO WIDODO DALAM KONTEKS POLITIK DINASTI - A, Widia Novita Lukitasari W; Agustini, Evi; Sailendra, Gilang; Lubis, Zaenal; Yunizhar, Mochammad Imam; Rusfiana, Yudi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The phenomenon of dynastic politics in Indonesia has become an important issue in the last few decades, especially during the leadership of President Joko Widodo (Jokowi). This article analyzes the influence of dynastic politics on Jokowi's leadership, with a focus on the involvement of his family members in local and national politics, such as Gibran Rakabuming Raka and Bobby Nasution. Although Jokowi has succeeded in steering Indonesia towards stable economic growth, the family's influence in politics has sparked debate about its impact on the quality of democracy. This research examines whether dynastic politics strengthens or weakens Indonesia's democratic system, by analyzing public perceptions, related legal regulations, and the impact on the regeneration of political leadership. Based on public opinion surveys, interviews with political experts, and literature analysis, this research concludes that dynastic politics, although supporting the continuation of family power, can reduce people's trust in a fair and competitive democratic process. This article provides policy recommendations to improve the regulation of dynastic politics in Indonesia, as well as encourage the renewal of a political system that is more open and based on meritocracy. ABSTRAKFenomena politik dinasti di Indonesia telah menjadi isu penting dalam beberapa dekade terakhir, terutama selama kepemimpinan Presiden Joko Widodo (Jokowi). Artikel ini menganalisis pengaruh politik dinasti terhadap kepemimpinan Jokowi, dengan fokus pada keterlibatan anggota keluarganya dalam politik lokal dan nasional, seperti Gibran Rakabuming Raka dan Bobby Nasution. Meskipun Jokowi berhasil membawa Indonesia menuju pertumbuhan ekonomi yang stabil, pengaruh keluarga dalam politik telah memicu perdebatan mengenai dampaknya terhadap kualitas demokrasi. Penelitian ini mengkaji apakah politik dinasti memperkuat atau justru melemahkan sistem demokrasi Indonesia, dengan menganalisis persepsi publik, regulasi hukum terkait, serta dampak terhadap regenerasi kepemimpinan politik. Berdasarkan survei opini publik, wawancara dengan pakar politik, dan analisis literatur, penelitian ini menyimpulkan bahwa politik dinasti, meskipun mendukung keberlanjutan kekuasaan keluarga, dapat mengurangi kepercayaan masyarakat terhadap proses demokrasi yang adil dan kompetitif. Artikel ini memberikan rekomendasi kebijakan untuk memperbaiki regulasi politik dinasti di Indonesia, serta mendorong pembaruan sistem politik yang lebih terbuka dan berbasis pada meritokrasi.